2016
DOI: 10.1186/s13568-016-0295-8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and stability of the d-amino acid substituted derivatives of antimicrobial peptide polybia-MPI

Abstract: Antimicrobial peptide has the potential to be developed as new kind of antimicrobial agents with novel action mechanism. However, the susceptibility to protease is a drawback for potential peptides to be clinical used. d-amino acid substitution can be one way to increase the proteolytic stability of peptides. In the present study, we synthesized the d-lysines substituted analog (d-lys-MPI) and the d-enantiomer of polybia-MPI (D-MPI) to improve the proteolytic resistance of polybia-MPI. Our results showed that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 35 publications
4
64
0
1
Order By: Relevance
“…Similar reports have shown that antibacterial peptides isolated from different microbial sources are able to persist at high temperatures without any change in the antimicrobial activity [23,24].…”
Section: Thermal Stability Of the Antibacterial Peptidesupporting
confidence: 65%
“…Similar reports have shown that antibacterial peptides isolated from different microbial sources are able to persist at high temperatures without any change in the antimicrobial activity [23,24].…”
Section: Thermal Stability Of the Antibacterial Peptidesupporting
confidence: 65%
“…This indicates that KK14 and its d ‐enantiomer do not use a specific receptor to inhibit fungal growth but rather use, at least partially, a membrane‐permeabilising mechanism. Although d ‐enantiomerization of a single residue can reduce haemolytic activity, full enantiomerization is usually more advised to avoid the loss of activity and structural deficiencies of the peptide as shown with polybia‐MPI . Interestingly, l and d ‐enantiomers of thanatin display the same antifungal activity, although the d ‐enantiomer is much less active against Gram‐negative bacteria …”
Section: Discussionmentioning
confidence: 99%
“…Finally, AMPs are known to have diverse modes of action depending on the bacterial targets they interact with and, therefore, are promising candidates for multi-target antibacterial treatments. Although these characteristics appear as promising features for drug development, some disadvantages have been pinpointed for AMP-based therapies, including chemical and physical instability (Zhao et al, 2016), proteolytic degradation (Pachon-Ibanez et al, 2017), short half-life and rapid elimination (Lombardi et al, 2015), slow tissue penetration (Koczulla et al, 2003), toxicity toward healthy human cells, and cell specificity (Oshiro et al, 2019). Based on that, an increasing number of computational strategies are underway, aiming at overcoming these obstacles by optimizing AMP sequences.…”
Section: Introductionmentioning
confidence: 99%